Method for Determining the Contrast of a Digital Image - S. S. Beknazarova; Z. R. Ishanxadjayeva (Periodica Journal, 2022)
Many of the developed methods and algorithms are associated with a wide variety of plots that have to be described using various mathematical models. In addition, the application of various optimality criteria also leads to the development of various filtration methods. Finally, in many cases, very often, due to mathematical difficulties, it is not possible to find the optimal image filtering procedure. The complexity of finding exact solutions leads to the generation of various variants of approximate methods of digital image analysis.
Keywords: many; models; complexity; solutions